E-Module Development of Line and Angle Materials Assisted by Learning Videos for Junior High School Students - Kartini Kartini; Rukiah Magdalena Hutabarat; Elfis Suanto (STAI Hubbulwathan Duri, 2022)
This study aimed to develop an E-Module on Line and Angle material with learning videos to facilitate the mathematical understanding ability of seventh-grade junior high school students that meets the aspects of validity and practicality requirements. This study was a research and development method with a 4D development model consisting of the define, design, develop, and disseminate stages. The small group trial subjects were nine students of grade VII at a Junior High School in Pekanbaru. The data collection instrument in this study consisted of a validity instrument in the form of a validation sheet and a practical instrument in the form of a student response questionnaire sheet. Based on the analysis of the validation sheet data and student response questionnaire sheets, the average E-Module validation was 3.6 with a very valid category, and the E-Module practicality average was 3.3 with a very practical category. Thus, it can be concluded that the developed E-Module is valid and practical.